Clinical Evaluation of Endorientation:Gravity related rectification for endoscopic images - Höller, Kurt Emmerich; Penne, Jochen; Hornegger, Joachim; Schneider, Armin; Gillen, Sonja; Feußner, Hubertus; Jahn, Jasper; Gutierrez, Javier; Wittenberg, Thomas (6th International Symposium on Image and Signal Processing and Analysis, ISPA 2009, 2009)
Providing a stable horizon on endoscopic images especially in non-rigid endoscopic surgery (particularly NOTES) is still an open issue. Image rectification can be realized with a tiny MEMS tri-axial inertial sensor that is placed on the tip of an endoscope. By measuring the impact of gravity on each of the three orthogonal axes the rotation angle can be estimated with some calculations out of these three acceleration values. Achievable repetition rate for angle termination has to be above the usual endoscopic video frame rate of 25-30Hz. The accelerometer frame rate can be set up to 400 Hz. Accuracy has to be less than one degree even within periods of high movement and superposed acceleration. Therefore an intelligent downsampling algorithm has to be found. The image rotation is performed by rotating digitally a capture of the endoscopic analog video signal. Improvements and benefits have been evaluated in a clinical evaluation: For different peritoneoscopic tasks time was taken and instrument position was tracked and recorded.